2015
DOI: 10.1097/iop.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms and Physical Deposits on Nasolacrimal Silastic Stents Following Dacryocystorhinostomy

Abstract: This is the first study to report the differences between ocular and nasal segments of lacrimal stents. These differences could propel further studies on stent biomechanics and their interactions with ocular and nasal tissues, following a dacryocystorhinostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Biofilms have been reported in both cases using mono® and bicanalicular stents. Further studies are needed in this grey area of canalicular stent selection [35][36][37][38]. In severe cases of primary canaliculitis with canalicular dilatation, the application of bicanalicular stents still came with favorable treatment outcomes in our study, while in mild or moderate cases of primary canaliculitis, monocanalicular stents may be theoretically more desirable.…”
Section: Discussionmentioning
confidence: 62%
“…Biofilms have been reported in both cases using mono® and bicanalicular stents. Further studies are needed in this grey area of canalicular stent selection [35][36][37][38]. In severe cases of primary canaliculitis with canalicular dilatation, the application of bicanalicular stents still came with favorable treatment outcomes in our study, while in mild or moderate cases of primary canaliculitis, monocanalicular stents may be theoretically more desirable.…”
Section: Discussionmentioning
confidence: 62%
“…It is not clear how long the stents should be left in place for optimal results. Studies on silastic stents used in DCR have shown that by 4 weeks, the stents become encased in biofilms, complex microbial communities, which could result in inflammation, infection and scarring 9, 10…”
Section: Discussionmentioning
confidence: 99%
“…They also demonstrated differential biofilm presence based upon the anatomical locations of the stent. 14 Becker 8 also noted differential culture growth between proximal and distal stent segments. Murphy et al 16 performed biofilm quantification on the extubated stents and found the mean biomass to be 0.9385 μm 3 /μm 2 (range, 0.3901-1.9511 μm 3 /μm 2 ).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have demonstrated polymicrobial biofilms on the surface and the lumen of the extubated lacrimal stents. 11–18 Interestingly, biofilms were also demonstrated on the stents obtained from culture-negative patients. 15 Biofilms were demonstrated as early as 3 weeks for Staphylococcus aureus and 4 weeks for P. aeruginosa in in-vitro studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation